ANALISIS BORAKS PADA MIE BASAH YANG DIJUAL DI KOTA MANADO - Payu, Muzdhalifah (PHARMACON, 2014)
Borax or the scientific name of sodium tetraborate decahydrate is known as a preservative known to the general public for preserving wood, wood antiseptic and cockroach control. Borax has accumulated harmful effects. In chronic poisoning can cause fever, anorexia, anuria, kidney damage, depression and confusion. The purpose of this study was to identify the compound borax on wet noodles are sold in the city of Manado. Sampling was done by taking 5 samples of wet noodles that are sold in the city of Manado. Identification is done by qualitative test flame test methods and turmeric paper and quantitative test methods UV-Vis spectrophotometry at Î» 553 nm. The results showed that the samples contained levels with borax, sample 1 == 264 g / mg, the second highest is 5 samples = 245.5 g / mg, is the third highest sample 2 = 243.5 g / mg, which is the fourth sample 4 = 206 g / mg and the fifth is a sample level 3 = 136 g / mg. Â  Key words : Borax, Wet Noodles, Qualitative, Manado